2011
DOI: 10.1017/s1742170511000469
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing cover crop mulches to reduce tillage in organic systems in the southeastern USA

Abstract: Organic systems in the southeastern USA offer unique challenges and solutions to crop production due to regional soil and climate characterized by highly weathered soil types, high precipitation and the capacity to grow cover crops in the winter. Recently, the interest of producers and researchers in high-residue cover crops and conservation tillage systems has increased. Various designs of the roller-crimper to manage cover crops have been invented and demonstrated to growers in the southeastern region of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
123
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(131 citation statements)
references
References 48 publications
7
123
1
Order By: Relevance
“…The two researchers concluded that small-grain cover crops could be killed effectively if rolling-crimping was delayed until advanced growth stages (Zadoks growth stage, ZGS 85; [30]). Recent roller-crimper designs have improved efficacy of killing cover crops and enhanced operator comfort when used in the field [31][32][33]. Current models can kill over 90% of a rye cover crop when terminated as early as 50% anthesis or ZGS 65 in some environments [34].…”
Section: Organic Zero Tillagementioning
confidence: 99%
See 1 more Smart Citation
“…The two researchers concluded that small-grain cover crops could be killed effectively if rolling-crimping was delayed until advanced growth stages (Zadoks growth stage, ZGS 85; [30]). Recent roller-crimper designs have improved efficacy of killing cover crops and enhanced operator comfort when used in the field [31][32][33]. Current models can kill over 90% of a rye cover crop when terminated as early as 50% anthesis or ZGS 65 in some environments [34].…”
Section: Organic Zero Tillagementioning
confidence: 99%
“…The enthusiasm generated among organic farmers spurred a growing number of researchers across North America to investigate organic ZT as an emerging cropping strategy. Results of several studies were summarized in a special issue on organic conservation tillage in Renewable Agriculture and Food Systems in 2012 [33,[37][38][39][40][41].…”
Section: Organic Zero Tillagementioning
confidence: 99%
“…Choosing early maturing cultivars is beneficial in allowing earlier termination and cash crop seeding in the spring [12]. Cultivar examples that are acceptable in certified organic systems include Québec-bred CETAB-HÂTIF, a fall rye variety that tends to bloom 7-10 days earlier than common fall rye, and North-Eastern USA-bred Purple Bounty and Purple Prosperity, hairy vetch varieties that bloom in late May as opposed to early June [9,34] (p. 88).…”
Section: Impact Of Cover Crop Termination In Organic No-till Systemsmentioning
confidence: 99%
“…Cultivar examples that are acceptable in certified organic systems include Québec-bred CETAB-HÂTIF, a fall rye variety that tends to bloom 7-10 days earlier than common fall rye, and North-Eastern USA-bred Purple Bounty and Purple Prosperity, hairy vetch varieties that bloom in late May as opposed to early June [9,34] (p. 88). Reberg-Horton et al compare rye varieties and find that an early maturing rye can have 25% more biomass than late maturing varieties even when the early maturing type is terminated in late April rather than in early May as for the late maturing variety [12].…”
Section: Impact Of Cover Crop Termination In Organic No-till Systemsmentioning
confidence: 99%
See 1 more Smart Citation